2010
DOI: 10.1159/000292019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Restraint Stress on Glucocorticoid Receptors in Mouse Spleen Lymphocytes: Involvement of the Sympathetic Nervous System

Abstract: Objective: Reciprocal pathways of interaction between the nervous and immune systems during stress may be regulated by stress-induced circulating glucocorticoids that act via type II glucocorticoid receptors (GRs). The aim of the present study was to investigate the effect of restraint stress on GRs in lymphocytes and the role of the sympathetic system in this effect. Methods: We used male Balb/c mice which were adrenalectomized 3 days before exposure to restraint stress (4 h). Specific binding of 3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Since CTL cells contributed to antitumor activity and the inhibition of cancer metastases , these results suggested that stress can facilitate cancer metastasis via a dysfunction of CTL cells. Numbers of studies reported that stress suppressed these immune functions (He et al, 2009b;Otten et al, 2010;Warner et al, 2010). Kurihara et al (2002) also reported that stress promoted tumorigenesis by reducing the number and impairing the lytic functions of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since CTL cells contributed to antitumor activity and the inhibition of cancer metastases , these results suggested that stress can facilitate cancer metastasis via a dysfunction of CTL cells. Numbers of studies reported that stress suppressed these immune functions (He et al, 2009b;Otten et al, 2010;Warner et al, 2010). Kurihara et al (2002) also reported that stress promoted tumorigenesis by reducing the number and impairing the lytic functions of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…The number of GCRs on mononuclear leukocytes correlates with hormone responsiveness [14] . Lymphocyte GCR levels are modulated by stress and communication between the nervous and immune systems [36] . More specifically, GCR expression is upregulated by catecholamines and corticosteroids [37,38] , hormones that increase during exercise.…”
Section: Discussionmentioning
confidence: 99%